Experimental ecological scheduling study on cascade hydropower station considering both fish spawning and hydropower generation - Wei, Guo; Liqiang, Yao; Guang Dong, Wu; Fu Ning, Cui; Jun, Shao; Yang Shuo, Ou; Tao, Du; Kun, Wang; Jun, Cao (Indian Journal of Fisheries, 2021)
In this study, a new ecological dispatching model for cascade hydropower stations considering fish reproduction is proposed by adding the ecological flow demand for fish spawning to the scheduling target of cascade hydropower stations. The study was conducted in the middle reaches of Jinsha River basin where Liyuan-Ahai cascade hydropower stations are located. By sorting out and analysing the habits and demands of aquatic organisms in the river along with the river water temperature and incoming water conditions, the hydrological and water temperature conditions suitable for experimental ecological regulation of the cascade section of the Jinsha River were obtained. Liyuan-Ahai cascade reservoirs were selected to carry out experimental ecological regulation simulations under different inflow scenarios. This study provides scientific basis and reference for cascade hydropower station dispatching, which can help restoration of the environment and satisfy optimal social and economic benefits. Keywords: Aquatic life demand, Cascade hydropower stations, Experimental ecological regulation